A nested quantitative PCR assay for detection of the hard clam pathogen Mucochytrium quahogii (=QPX) in environmental samples - Geraci-Yee, Sabrina; Allam, Bassem; Collier, Jackie L. (Frontiers in Marine Science, 2022)
Progress in understanding and managing QPX disease outbreaks in hard clams (Mercenaria mercenaria) has been limited by lack of insight into basic aspects of the biology and ecology of the opportunistic pathogen Mucochytrium quahogii (formerly QPX or Quahog Parasite Unknown). One barrier is that while several methods have been able to detect M. quahogii in seawater and sediment, its abundance was typically too low for reliable quantification by those methods. Here we describe the development and validation of a sensitive, M. quahogii-specific, nested quantitative PCR (nqPCR) assay following the Minimum Information for Publication of Quantitative Real-Time PCR Experiments (MIQE) guidelines. The assay reaches the theoretical limit of detection (LOD) of a PCR assay at 3 copies per reaction with excellent efficiency, linearity, and minimal sample PCR inhibition. The functionality of the assay was evaluated by quantifying M. quahogii in sediment and seawater samples, which revealed that M. quahogii was broadly distributed throughout the marine environment, detected in 75% of samples, with mean estimated abundance of 0.21 cells per mg sediment, 0.55 cells per ml bottom seawater, and 0.02 cells per ml surface seawater. M. quahogii was most prevalent and most abundant in sediment and bottom seawater samples, suggesting that the flocculent layer at the sediment-water interface is an important environmental reservoir where M. quahogii may interact with hard clams. This assay will serve as a valuable tool to better understand QPX disease dynamics and offers a model to guide development of similar assays for other important marine microbes typically present at similarly low abundance.